Оцінка зношування контактних напайок з композиційних матеріалів контакторів електровозів змінного струму - Тетерко, О.А.; Баб’як, М.О.; Синявський, Т.Й. (Электрические контакты и электроды, 2010)
Розглянуто результати експериментальних досліджень технологічного та експлуатаційного зношування контактних напайок. Визначено ймовірність безвідмовної роботи за критерієм товщини напайки при різних пробігах електровозів для різних матеріалів контактних напайок, а також отримано γ-відсотковий ресурс контактів. Рассмотрены результаты экспериментальных исследований технологического и эксплуатационного изнашивания контактных напаек. Определена вероятность безотказной работы по критерию толщины напайки при разных пробегах электровозов для различных материалов контактных напаек, а также получен γ-процентный ресурс контактов. The results of experimental researches of technological and operating wear of contact brazing are resulted in work. It is indicated on the negative sides of repair treatment of contact brazing, but also its necessity is argued. The features of wear of contact brazing from different materials are considered. Probability of faultless work after the criterion of thickness of brazing at the different runs of electric locomotives for different materials of contact brazing, and also γ-percent resource of contacts is got. Histograms and theoretical laws of distributing of runs l of electric locomotives are resulted to the refuse of contacts from the probed materials. A conclusion is given in relation to the most reliable and lasting material for brazing on the contacts of contactors EKG-8 and PC-96-101.